The influence of genetics in sickle cell disease for family construction (Research, Society and Development, 2023)
OBJECTIVE: To verify the knowledge of people with sickle cell disease, of reproductive age, about the influence of the disease's genetics on their family construction. METHODOLOGY: Descriptive, exploratory and qualitative research. The study had 20 participants diagnosed with sickle cell disease at reproductive age. Interviews were conducted, data analysis was performed using Bardin's content analysis and categorization using the IRaMuTeQ software. RESULTS: There was concern about the possibility of the children having sickle cell disease. In addition, the participants stated that they believed that sickle cell disease influences their family construction and demonstrated good knowledge about the cause and inheritance of the disease. FINAL CONSIDERATIONS: The words that emerged in the similarity tree supported the inference that although most participants have a satisfactory level of knowledge about the disease itself, there is still a weakness in basic concepts that perpetuate erroneous and stigmatized conceptions about the disease. In addition, it was observed that there is a constant feeling of concern related to the risk of having children with sickle cell disease, the difficulty in caring for a child who may inherit the disease and how these contingencies influence the family planning process.